TENSILE STRENGTH IN DIFFERENT DIRECTIONS OF LAMINATED PLYWOOD MADE FROM BEECH VENEERS (Innovation in Woodworking Industry and Engineering design, 2026)
Тhe aim of the research presented in this paper is to study the tensile properties at different directions of experimental plywood.For this research nine-layered plywood is made. The model is made from peeled beech veneers with thickness of 1,2; 1,5; 2,2 and 3,2 mm.Pure water-soluble phenol-formaldehyde resin is used as plywood binder.The tensile strength of the plywood panel is tested in five directions, i.e., parallel and per-pendicular to the face grain, and at the angles of 22,5º; 45º and 67,5º to the face grain of the panel.Coefficients of the equality of the tensile strength in different directions of the plywood model is calculated trough polar diagram made on the basis of the obtained data for the tensile strength at different angles to the face grain of plywood. The coefficient of mass quality is calculated too.The research results showed that the experimental plywood model meet and exceed the defined values of tensile strength in accordance with the requirements of the standard for load-bearing plywood for use in construction.